Characterization of the clinical relevance and hypoallergenic peptides of the newly evidenced major allergen Hum j 1 - Cheng, Ya-Li; Li, Qiong; Yang, Yong-Shi; Hou, Yi-Bo; Xu, Zhi-Qiang; Wei, Ji-Fu; Sun, Jin-Lyu (Frontiers in Immunology, 2025)
BackgroundHumulus japonicus (HJ) pollen is a predominant autumn allergen in northern China. Two decades ago, a 10 kDa protein termed Hum j 1 was proposed as a major allergen, but its uncertainty hindered its clinical application. This study aims to investigate the clinical relevance of Hum j 1 and screen hypoallergenic peptides for potential application in molecular diagnosis and immunotherapy.MethodsSerum samples from 93 HJ pollen-allergic patients were analyzed for IgE reactivity against recombinant Hum j 1 (rHum j 1). We evaluated correlations between IgE responses to rHum j 1 and HJ pollen crude extracts using Spearman’s rank correlation analysis. The association between clinical symptoms and Hum j 1-IgE positivity was evaluated by group comparisons and multivariable analyses. Allergenicity of Hum j 1 was further investigated by immunoblotting and basophil activation tests. Six KLH-coupled peptides (21–25 amino acids) spanning the complete Hum j 1 sequence were synthesized to assess hypoallergenicity and IgG-mediated inhibitory effects against allergen-specific IgE binding using a murine passive immunization model.ResultsrHum j 1 demonstrated IgE reactivity in 74.2% (69/93) of the patients and induced significant basophil activation. rHum j 1-specific IgE levels showed a moderate positive correlation with crude extract-specific IgE levels (Spearman’s ρ = 0.529, p < 0.0001). Patients with allergic rhinitis complicated by asthma had significantly higher levels of Hum j 1-sIgE (p = 0.014). We found a significant association between Hum j 1 sensitization and asthma in the multivariate analysis [odds ratio (OR) = 3.98, 95% confidence interval (CI): 1.2–13.0, p = 0.02], with Hum j 1-sensitized patients showing higher asthma prevalence compared to non-sensitized individuals (46% vs. 17%, p = 0.010). All six peptides showed significantly reduced IgE reactivity (p < 0.0001) and minimal basophil activation. Immunized mice produced high-titer IgG antibodies that inhibited patient IgE binding to rHum j 1 by 22.09%–64.61%.ConclusionsHum j 1 could enhance the sensitivity of HJ pollen crude extract-based IgE assays. IgE reactivity to Hum j 1 was more frequently associated with allergic asthma. The hypoallergenic linear peptides of Hum j 1 laid the foundation for the development of a molecular vaccine for allergen-specific immunotherapy. These findings would contribute to developing diagnostic and therapeutic strategies for HJ pollinosis.